Frequency, Predictors, Distribution, and Morphological Characteristics of Layered Culprit and Nonculprit Plaques of Patients With Acute Myocardial Infarction: In Vivo 3-Vessel Optical Coherence Tomography Study. (October 2020) - Dai, Jiannan; Fang, Chao; Zhang, Shaotao; Li, Lulu; Wang, Yini; Xing, Lei; Yu, Huai; Jiang, Senqing; Yin, Yanwei; Wang, Jifei; Wang, Yidan; Guo, Junchen; et al.
Abstract : Background: Subclinical atherothrombosis and plaque healing may lead to rapid plaque progression. The histopathologic healed plaque has a layered appearance when imaged using optical coherence tomography. We assessed the frequency, predictors, distribution, and morphological characteristics of optical coherence tomography layered culprit and nonculprit plaques in patients with acute myocardial infarction. Methods: A prospective series of 325 patients with acute myocardial infarction underwent optical coherence tomography imaging of all 3 native coronary arteries. Layered plaque phenotype had heterogeneous signal-rich layered tissue located close to the luminal surface that was clearly demarcated from the underlying plaque. Results: Layered plaques were detected in 74.5% of patients with acute myocardial infarction. Patients with layered culprit plaques had more layered nonculprit plaques; and they more often had preinfarction angina, ST-segment–elevation myocardial infarction, higher low-density lipoprotein cholesterol, and absence of antiplatelet therapy. Layered plaques tended to cluster in the proximal segment of the left anterior descending artery and left circumflex artery but were more uniformly distributed in the right coronary artery. As compared with nonlayered plaques, layered plaques had greater optical coherence tomography lumen area stenosis at both culprit and nonculprit sites. The frequency of layered plaque phenotype ( P =0.038) and maximum area of layered tissue ( P <0.001) increased from nonculprit thin-cap fibroatheromas to nonculprit ruptures to culprit ruptures. Conclusions: Layered plaques were identified in 3-quarters of patients with acute myocardial infarction, especially in the culprit plaques of patients with ST-segment–elevation myocardial infarction. Layered plaques had a limited, focal distribution in the left anterior descending artery, and left circumflex artery but were more evenly distributed in the right coronary artery and were characterized by greater lumen narrowing at both culprit and nonculprit sites. Abstract : Supplemental Digital Content is available in the text.